The Role of Islamic Education in Preventing Academic Procrastination Among College Students Who Use Online Loans - Rizqy Indra Maulana; Naelul Mubarok (Jurnal Ragam Pengabdian, 2026)
The increasing use of online loans among university students has raised concerns about its impact on academic behavior, particularly academic procrastination. Financial pressures from loan repayments may lead students to delay academic tasks and prioritize financial matters over their educational responsibilities. This study aims to analyze the role of Islamic Religious Education in preventing academic procrastination among students who use online loans at Universitas Negeri Jakarta. A qualitative case study approach was employed, with data collected through interviews, observations, and documentation involving students and Islamic Religious Education lecturers. The findings indicate that students experienced academic procrastination in the form of delaying assignments, avoiding difficult tasks, and focusing on financial concerns. Islamic Religious Education contributed to reducing procrastination through the internalization of values such as discipline, responsibility, amanah (trustworthiness), time management, and self-control. These values helped students manage their academic obligations more effectively despite financial challenges. The study concludes that Islamic Religious Education plays an important role in preventing academic procrastination and strengthening students’ character development.